Partners in biological control of cocoa pests: mutualism between Dolichoderus thoracicus (Hymenoptera: Formicidae) and Cataenococcus hispidus (Hemiptera: Pseudococcidae) - Ho, C. T.; Khoo, K. C. (Cambridge University Press, 1997)
The observed mutualistic relationship between the black cocoa ant Dolichoderus thoracicus (Smith) and the mealybug Cataenococcus hispidus (Morrison) was examined. The importance of C. hispidus to D. thoracicus as a food source was investigated by giving D. thoracicus access to C. hispidus only, to C. hispidus and other food sources, and denying access to any obvious food sources. Dolichoderus thoracicus was seen to depend on C. hispidus alone as a source of food over an eight-week period of observation without showing ill effects. The role of D. thoracicus in spreading C. hispidus was studied in an experiment consisting of combinations of D. thoracicus and C. hispidus exclusion. It was shown that D. thoracicus was responsible for carrying C. hispidus across a ‘mealybug excluder’. Data on the frequency and duration of transport of C. hispidus by D. thoracicus were obtained by direct observation for a total of 90 h over 17 days. Both adults and nymphs of C. hispidus were carried by D. thoracicus with its mandibles in a brief and erratic manner, in the general direction of the trail. Such transportation is nevertheless considered to be important in view of the large number of individuals of D. thoracicus moving along a trail. The close mutualistic relationship between D. thoracicus and C. hispidus reiterates the necessity to manipulate both organisms for control of cocoa pests.